2006
DOI: 10.1103/physrevb.74.045126
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between thermodynamical stabilities of metal borohydrides and cation electronegativites: First-principles calculations and experiments

Abstract: The thermodynamical stabilities for the series of metal borohydrides M͑BH 4 ͒ n ͑M = Li, Na, K, Cu, Mg, Zn, Sc, Zr, and Hf; n =1-4͒ have been systematically investigated by first-principles calculations. The results indicated that an ionic bonding between M n+ cations and ͓BH 4 ͔ − anions exists in M͑BH 4 ͒ n , and the charge transfer from M n+ cations to ͓BH 4 ͔ − anions is a key feature for the stability of M͑BH 4 ͒ n . A good correlation between the heat of formation ⌬H boro of M͑BH 4 ͒ n and the Pauling el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
523
4
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(576 citation statements)
references
References 47 publications
32
523
4
6
Order By: Relevance
“…As in case of the aluminium hydrides there are two different possibilities for substitution in these complex hydrides: cation substitution and anion substitution. Nakamori et al (Nakamori et al, 2006) …”
Section: Borohydridesmentioning
confidence: 99%
“…As in case of the aluminium hydrides there are two different possibilities for substitution in these complex hydrides: cation substitution and anion substitution. Nakamori et al (Nakamori et al, 2006) …”
Section: Borohydridesmentioning
confidence: 99%
“…Nakamori et al [33] studied theoretically the stabi-lity of metal-borohydrides and found a correlation between the heat of formation and the Pauling electronegativity of the cation. The value reported for LiBH 4 was D f H (0 K)¼ 146 kJ mol 1 .…”
Section: Standard Enthalpy Of Formationmentioning
confidence: 99%
“…The ionic radii were taken from literature. [44][45][46][47] The radius of the ion with an underlined name is connected to the horizontal axis. The general trend that is observed in all three series (X + PSS − ; TBA + Y − ; TBA + Z − ) is that an increase in ion size is accompanied by a reduction in the magnitude of the work function modifi cation.…”
Section: Ion Size Effects In Wmlsmentioning
confidence: 99%